THE INFLUENCE OF WORK DISCIPLINE, WORK MOTIVATION, AND ORGANIZATIONAL COMMITMENT ON SATISFACTION EMPLOYEE WORK H&M CENTRE POINT MEDAN - Pahlepi Siregar; Ahmad Azmi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The objective of this study is to determine the impact of work discipline, work motivation, and organizational commitment, both individually and collectively, on the job satisfaction of employees at H&M Center Point Medan. The study population consisted of 54 employees, all of whom were included as respondents in the sample. The employed sampling technique is saturated sampling. The collection of primary data involved the use of a questionnaire, which was subsequently subjected to quantitative analysis using the multiple linear regression method with the assistance of the SPSS 24.0 software. The research findings indicate that work discipline, work motivation, and work commitment have a substantial and positive impact on job satisfaction among employees at H&M CENTER POINT MEDAN. Furthermore, when considered together, work discipline, work motivation, and work commitment collectively contribute significantly to job satisfaction